PROTECTION OF HEALTH AND EMPLOYMENT GUARANTEE RIGHTS FOR PERSONS WITH DISABILITIES IN INDONESIA - Khalfia, Khalfia; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT The situation of persons with disabilities as a vulnerable group experiences many abuses of their rights. Among these are the right to obtain health services and work. People with disabilities experience a lot of discrimination in fulfilling their rights. Discrimination in fulfilling these rights makes life difficult for people with disabilities. Therefore, they need health and job guarantees from the government to guarantee their lives. Currently, the number of people with disabilities in Indonesia has reached 22.97 million people or around 8.5% of Indonesia's population, with the highest number of people with disabilities in old age. The living conditions of people with disabilities are also still worrying, considering that the majority are still in families whose living needs are not met (poor). This research aims to collect and analyze articles related to protecting the rights to health and employment security for people with disabilities. The design used is a literature review, where articles are collected using the Google Scholar database. The criteria for articles used are those published in 2016-2023. Based on the articles collected, the results show that the government has implemented the protection of the rights to health insurance and employment for people with disabilities. However, its implementation is still less than optimal. Keywords: Disability, Health, Employment Guarantees, Protection of Rights